Landscape of alternative splicing in Capra_hircus. Issue 1 (December 2018) - Xu, Tieshan; Xu, Feng; Gu, Lihong; Rong, Guang; Li, Mao; Qiao, Fei; Shi, Liguang; Wang, Dingfa; Xia, Wanliang; Xun, Wenjuan; Cao, Ting; Liu, Yiming; et al.
Abstract Alternative splicing (AS) is a fundamental regulatory process in all higher eukaryotes. However, AS landscapes for a number of animals, including goats, have not been explored to date. Here, we sequenced 60 samples representing 5 tissues from 4 developmental stages in triplicate using RNA-seq to elucidate the goat AS landscape. In total, 14, 521 genes underwent AS (AS genes), accounting for 85.53% of intron-containing genes (16, 697). Among these AS genes, 6, 342 were differentially expressed in different tissues. Of the AS events identified, retained introns were most prevalent (37.04% of total AS events). Functional enrichment analysis of differential and specific AS genes indicated goat AS mainly involved in organ function and development. Particularly, AS genes identified in leg muscle were associated with the "regulation of skeletal muscle tissue development" GO term. Given genes were associated with this term, four of which (NRG4, IP6K3, AMPD1, andDYSF ) might play crucial roles in skeletal muscle development. Further investigation indicated these five genes, harbored 13 ASs, spliced exclusively in leg muscle, likely played a role in goat leg muscle development. These results provide novel insights into goat AS landscapes and a valuable resource for investigation of goat transcriptome complexity and gene regulation.